(untitled) (Research, Society and Development, 2021)
Objective: Analyze and disclose the experience and challenges of two volunteers, during the immunization campaign against COVID-19, at a vaccination post, located in the Metropolitan Region of Belém. Methodology: This is a descriptive study, with a qualitative approach, of the experience report type, carried out by academics and volunteer professionals from different courses, with prevalence in the health area, during the vaccination campaign against COVID-19, in the city of Belém -PA, from February to April 2021. Result: Carried out in an extramural environment, the vaccination campaign against Covid-19 faced several challenges for its realization, among them: the logistic organization of the physical space for the conditioning of people, the reception and its humanization, as well as its subdivisions and bilateral interaction between professionals and future vaccinated people and their families. Conclusion: There is a need for greater depth on the subject with the adoption of new research on the current scenario in an attempt to minimize the problems encountered and, consequently, streamline and collaborate with the process of adherence to vaccination by the population.